Pengaruh Penggunaan Katup Ekspansi Jenis Kapiler Dan Termostatik Terhadap Tekanan Dan Temperatur Pada Mesin Pendingin Siklus Kompresi Uap Hibrida Menggunakan Refrigeran 22 - Mainil, Rahmat Iman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hybrid system is the system that can increase the energy efficiency by recovering waste energy of energy conversion machine. This research aims to investigate the vapor compression refrigeration machine performance that obtained by using capillary expansion valve, thermostatic expansion valve, and addition of hotspot water heater (HWH). The test was conducted with four variations of test, such as using capillary in standard condition, using thermostatic in standard condition, using capillary with HWH, and using thermostatic with HWH. The pressure and temperature data were collected in every 5 minutes during 120 minutes of operation. The results showed that the compressor pressures when using capillary and thermostatic types of expansion valve in standard condition were obtained at 340 Psia and 350 Psia. Meanwhile, the compressor pressures when using HWH addition were obtained at 350 Psia and 291 Psia. The capillary expansion valve pressures in standard condition and with HWH were increased by 4.50 % and 11.13 % respectively to the thermostatic pressures. The compressor temperatures using capillary in standard condition decreased by 4.03 %, but using capillary in HWH condition increased by 1.60 % to the thermostatic temperatures. The inlet temperature of HWH coil using thermostatic was increased by 2.31 % to the temperature of coil while using capillary. Meanwhile, the outlet temperature was decreased by 11.22 %.Keywords: Expansion Valves, Pressure, Temperature, and HWH